Lung lymphatic endothelial cells undergo inflammatory and prothrombotic changes in a model of chronic obstructive pulmonary disease - Trivedi, Anjali; Lu, Tyler M.; Summers, Barbara; Kim, Kihwan; Rhee, Alexander J.; Houghton, Sean; Byers, Derek E.; Lis, Raphaël; Reed, Hasina Outtz (Frontiers in Cell and Developmental Biology, 2024)
The lymphatic vasculature regulates lung homeostasis through drainage of fluid and trafficking of immune cells and plays a key role in the response to lung injury in several disease states. We have previously shown that lymphatic dysfunction occurs early in the pathogenesis of COPD caused by cigarette smoke (CS), and that this is associated with increased thrombin and fibrin clots in lung lymph.However, the direct effects of CS and thrombin on lymphatic endothelial cells (LECs) in COPD are not entirely clear. Studies of the blood vasculature have shown that COPD is associated with increased thrombin that causes endothelial dysfunction after CS exposure, and that is characterized by changes in expression of coagulation factors and leukocyte adhesion proteins. Here, we sought to determine whether similar changes occur in LECs. We used an in vitro cell culture system and treated human lung microvascular lymphatic endothelial cells with cigarette smoke extract (CSE) and/or thrombin.We found that CSE treatment led to decreased fibrinolytic activity in LECs which was associated with increased expression of plasminogen activator inhibitor 1 (PAI-1). LECs treated with both CSE and thrombin together had decreased expression of TFPI and increased expression of vascular adhesion molecules. RNA Sequencing of lung LECs isolated from mice exposed to CS also showed upregulation of prothrombotic and inflammatory pathways at both acute and chronic timepoints.Analysis of publicly available single cell RNA Sequencing of LECs as well as immunohistochemical staining of lung tissue from COPD patients supported these data and showed increased expression of inflammatory markers in LECs from COPD patients compared to control. These studies suggest that in parallel with blood vessels, the lymphatic endothelium undergoes inflammatory changes associated CS exposure and increased thrombin in COPD. Further research is needed to unravel the mechanisms by which these changes affect lymphatic function and drive tissue injury in COPD.